Testing the Impact of the Worksite Heart Health Improvement Project on Cardiovascular Disease Risk Factors Over Time. Issue 8 (August 2018) - Doran, Kelly; Resnick, Barbara; Zhu, Shijun; Alghzawi, Hamzah
Abstract : Objective: We aimed to test the impact of the Worksite Heart Health Improvement Project (WHHIP) on cardiovascular risk factors among long-term care staff. Methods: The WHHIP was an 18-month cluster randomized control trial conducted in four long-term care facilities ( n = 98). Results: A significant positive delayed intervention effect for diastolic blood pressure was seen in the intervention group (80.34 mm/Hg [standard deviation SD = 6.10] at baseline to 73.08 mm/Hg [SD = 4.99] at 18-months; P = <0.001). Whereas, a significant negative intervention effect was seen for steps with a mean increase from 5807.18 (SD = 3934.30) steps at baseline to 7839.19 (SD = 3126.09) steps at 18-months ( P = 0.022) as well as body mass index with a mean change from 29.86 (SD = 7.38) at baseline to 26.67 (SD = 5.29) at 18-months ( P = 0.045) in the education only group. Conclusion: The WHHIP demonstrated the ability to impact participants' blood pressure over time.